Biofunctionalization of titanium surface with multilayer films modified by heparin‐VEGF‐fibronectin complex to improve endothelial cell proliferation and blood compatibility 1. Issue 2 (3rd August 2012) - Wang, H. G.; Yin, T. Y.; Ge, S. P.; Zhang, Q.; Dong, Q. L.; Lei, D. X.; Sun, D. M.; Wang, G. X.
Abstract: In‐stent restenosis and subsequent thrombosis remain a significant complication following the implantation of coronary stents. Different approaches have been used in developing novel coronary stents to protect against thrombosis and minimize restenosis. In the present study, we designed a biomacromolecular layer‐by‐layer coating with heparin, vascular endothelial growth factor (VEGF), and fibronectin onto nickel‐free titanium surface to improve blood compatibility and endothelial cell proliferation. The multilayer assembling process was monitored by water contact angle and surface plasmon resonance, respectively. With increasing the number of layers, the deposition of polyelectrolyte as self‐assembled ultrathin multilayer films showed linear growth of absorbance. In vitro blood compatibility results revealed that the fabricated layers prolonged activated partial thrombin time and prothrombin time, reduced platelets activation and aggregation, and reduced blood hemolysis rate. Cell adhesion and growth results showed that the assembled multilayer films significantly promoted cell attachment and growth, and the endothelialization property of the multilayer films was preferable compared with the untreated titanium disk. In conclusion, these results suggest that titanium surface modification using biofunctional multilayer films composed of heparin, VEGF, and fibronectin may serve as a potential approach to inhibit thrombosis and promote re‐endothelialization of cardiovascular stents. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.